Properties of melt processed chitosan and aliphatic polyester blends - Correlo, V. M. (2005)
The activities (at pH 7 and 50°C) of purified EGV (Humicola insolens) and CenA (Cellulomonas fimi) were determined on cotton fabrics at high and low levels of mechanical agitation. Similar activity measurements were also made by using the core domains of these cellulases. Activity experiments suggested that the presence of cellulose binding domains (CBDs) is not essential for cellulase performance in the textile processes, where high levels of mechanical agitation are applied. The binding reversibilities of these cellulases and their cores were studied by dilution of the treatment liquor after equilibrium adsorption. EGV showed low percentage of adsorption under both levels of agitation. It was observed that the adsorption/desorption processes of cellulases are enhanced by higher mechanical agitation levels and that the binding of cellulase with CBD of family I (EGV) is more reversible than that of CBD of the cellulase of family II (CenA).